Enzymatic studies on Natural rubber biodegradation by Bacillus pumilus - G, Nayanashree; B, Thippeswamy; M, Krishnappa (International Journal of Biological Research, 2014)
Objective: To isolate Natural Rubber degrading Bacteria from soil and to screen the enzymes responsible for Natural Rubber degradation. Methods: Soil burial method was followed for isolation of bacteria. Plate assay method and liquid assay method by using Mineral Salt Medium was followed for screening of bacteria for its capacity to degrade Natural rubber. Degradation was confirmed by weight loss experiment, Scanning Electron Microscopy (SEM) and Fourier Transform Infra-Red (FTIR) studies. Enzymes responsible for Natural rubber degradation were screened and their activity was measured by spectrophotometric method. Results: Isolated organism was identified as Bacillus pumilus. It was able to degrade Natural rubber which was confirmed by weight loss, SEM and FTIR studies. From the current work it was studied that Laccase and Manganese peroxidase were the enzymes which were responsible for Natural rubber degradation. Conclusion: From current investigation, it can be concluded that our isolated bacterial strain Bacillus pumilus have the capacity to degrade Natural rubber and it can be useful in solving the problem caused by waste Natural rubber products in the environment. Keywords: Bacillus Pumilus, Hevea Brasiliensis, Polyisoprene, Laccase, Manganese Peroxidase.